Type 2 diabetes diminishes the benefits of dietary antioxidants: Evidence from the different free radical scavenging potential. (1st November 2015) - Cao, Hui; Xie, Yixi; Chen, Xiaoqing
Highlights: The plasma proteins from type 2 diabetics bind and protect the antioxidants less than the ones in healthy blood do. Diabetes diminishes the benefits of dietary polyphenols. There are no obvious affinity–activity relationships of plasma protein–polyphenols systems as free radical scavengers. Abstract: The development of food fortified with polyphenols and polyphenol-rich foods represents a novel approach for preventing or managing type 2 diabetes. Herein, taking advantage of several radical scavenging, the impact of plasma proteins in diabetes on the benefits of dietary polyphenols was investigated. It illustrated that plasma proteins masked the dietary polyphenols, thus reducing their radical scavenging potential. The plasma proteins from type 2 diabetics bind and protect (i.e., mask) the polyphenol antioxidants less effectively than the non-glycosylated ones in healthy blood do. In the blood of diabetics the less-protected (non-masked) antioxidants react with free radicals before being delivered to the tissues that need them. We should pay more attention to in vivo benefits of dietary polyphenols for type 2 diabetics.